2010
DOI: 10.1007/978-3-642-11876-0_30
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Biped Walking Using Truncated Fourier Series and Particle Swarm Optimization

Abstract: Abstract. Controlling a biped robot with a high degree of freedom to achieve stable and straight movement patterns is a complex problem. With growing computational power of computer hardware, high resolution real time simulation of such robot models has become more and more applicable. This paper presents a novel approach to generate bipedal gait for humanoid locomotion. This approach is based on modified Truncated Fourier Series (TFS) for generating angular trajectories. It is also the first time that Particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
14
0
3
Order By: Relevance
“…For instance, two different gait definition methods, a finite state machine based on the joint angles of the robot legs, and an Elman's recurrent neural network were studied [80], and the performance of the neural controller was reported superior (more stable, better displacement) for a simulated legged robot navigating on an irregular surface. TFS has also been reported to be a good gait representation approach and has been mentioned above [76].…”
Section: Studying Ec Approaches That Are Gait Optimizationmentioning
confidence: 95%
See 3 more Smart Citations
“…For instance, two different gait definition methods, a finite state machine based on the joint angles of the robot legs, and an Elman's recurrent neural network were studied [80], and the performance of the neural controller was reported superior (more stable, better displacement) for a simulated legged robot navigating on an irregular surface. TFS has also been reported to be a good gait representation approach and has been mentioned above [76].…”
Section: Studying Ec Approaches That Are Gait Optimizationmentioning
confidence: 95%
“…These also search for the global optimum of the cost function without using the differential information of a given cost function. Particle Swarm Optimization (PSO) can be used to optimize the stable and straight movement patterns (gaits) of a humanoid robot with the control signals of the joint angles produced by a Truncated Fourier Series (TFS) [75,76]. It is reported that PSO optimized TFS significantly faster and better than GA to generate straighter and faster humanoid locomotion because PSO bypassed a local minimum that GA was caught in [76].…”
Section: Comparing Ec With Other Global Optimization Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have focused on this issue and a lot of approaches have been presented. There are two major approaches in bipedal walking researches; model-based and model-free approaches [2,3]. In model-based approach, the designer first derives the model of the robot and then builds a controller for the model.…”
Section: Introductionmentioning
confidence: 99%